2006
DOI: 10.1021/la052772k
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Composition and Structural Parameters of Water/C12-s-C12·2Br/n-Hexanol/n-Heptane Microemulsions Studied by the Dilution Method

Abstract: The interfacial composition of the stable water/C12-s-C12 x 2Br/n-hexanol/n-heptane microemulsions has been studied in detail by dilution method. The results showed a marked maximum amount of the n-hexanol populating on the surfaces of droplets (represented as a = n(a)i/n(s), where n(a)i and n(s) are respectively the moles of n-hexanol and gemini surfactant on the surface of droplets) with increasing water content. At a constant level of water addition (the molar ratio of water to surfactant W0 = 20), a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
47
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 47 publications
16
47
0
Order By: Relevance
“…In other words, association between surfactant and cosurfactant molecules at the interface becomes less favourable with increase in ω [36]. This type of variation was reported by and Paul and Nandy [36] and Zheng et al [45]. Earlier, Hait [46].…”
Section: Steady State Fluorescence Anisotropy Measurementmentioning
confidence: 55%
See 1 more Smart Citation
“…In other words, association between surfactant and cosurfactant molecules at the interface becomes less favourable with increase in ω [36]. This type of variation was reported by and Paul and Nandy [36] and Zheng et al [45]. Earlier, Hait [46].…”
Section: Steady State Fluorescence Anisotropy Measurementmentioning
confidence: 55%
“…As a result, the effective packing parameter of the surfactant (P) is decreased [78,89]. From theoretical analysis, it has been observed that smaller P requires higher amount of alkanol for formation of microemulsions [45]. Hence, n a i values are found to be higher for IBB stabilized systems compared to LIM systems.…”
Section: Comprehension On Overall Results From Perspective Of Oil Chamentioning
confidence: 99%
“…The concentrations of cosurfactant at the interface and in the bulk oil phase were estimated to get the distribution constant (K d ) by the dilution experiments in the light of the physicochemical rationale elaborated by Moulik and Hait [43], Bayrak [44], Mitra et al [45] and Zheng et al [39]. The total number of moles of the cosurfactant, n a present in the stable microemulsion is given by Eq.…”
Section: Theoretical Premise and Mathematical Model Dilution Experimementioning
confidence: 99%
“…The thermodynamic properties of microemulsion can exert significant effects on the size of nanoparticles [38]. Also, the adjustable droplet size was proposed to be useful for preparing metal nanoparticles of different sizes using W/O microemulsions as templates [39]. The above mentioned parameters were determined from this pioneering method.…”
Section: Introductionmentioning
confidence: 99%
“…www.intechopen.com During 1980s the "dilution method" was well adopted by many, to extract energetic information for different combinations along with the understanding of their structural features (Bansal et al, 1979;Birdi, 1982;Singh et al, 1993;Bayrak, 2004;Zheng et al, 2006;Zheng et al, 2007), after it was first introduced by Schulman group (Bowcott & Schulman, 1955;Schulman et al, 1959). Basically, this method deals with the estimation of distribution of cosurfactant (k d ) and hence, determines the composition of interphase which is in turn responsible for the formation and stability of microemulsions.…”
Section: Basics Of Microemulsion Formationmentioning
confidence: 99%